Design and Application of PLC-Based Salinocontrol Machine Integrated with IoT for Milkfish Ponds in Ujung Watu Village, Jepara - Ahmad Faidlon; Aida Nahar; Anna Widiastuti; Haris Fujiari; Riyan Agus Prasetiyo (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2025)
Milkfish farming in coastal ponds of Ujung Watu Village, Jepara, is highly influenced by the stability of water salinity levels. Significant fluctuations in salinity can interfere with the growth and health of fish, so an adaptive control system is needed. Research methods include field data collection, hardware and software design, and system testing in an active pond for 14 days (23-hour sampling), where data is extracted for 23 hours. The system uses a salinity sensor to detect water conditions, PLC to automatically control the brackish water pump, while wireless remote control uses IoT, in addition to controliing, IoT to send data to the Android-based monitoring platform. The test results show that this machine is able to maintain salinity levels within the optimal range of 10000-30000 ppm, and provide remote monitoring convenience to pond farmers. The monitoring system serves as a predictive for manual wireless control of electric pumps (IoT), while automatic control is controlled by PLC.